The relationship between Bornean orangutans’ (Pongo pygmaeus) population and land cover change in West Kalimantan, Indonesia - IDA PARIDA; YANTO SANTOSA; I NENGAH SURATI JAYA (Society for Indonesian Biodiversity, 2024)
Abstract. Parida I, Santosa Y, Jaya INS. 2024. The relationship between Bornean orangutans’ (Pongo pygmaeus) population and land cover change in West Kalimantan, Indonesia. Biodiversitas 25: 1831-1837. Orangutans (Pongo pygmaeus Linnaeus 1760) are critically endangered species under IUCN Red List and classified in Appendix 1 of CITES. Their population is declining, which is largely caused by habitat loss. This study aims to investigate the population dynamics of the Bornean orangutans and changes in land cover in West Kalimantan and to analyze the relationship between the orangutan population and land cover change. Bornean orangutan population data from 2014 to 2019 at four locations (i.e. Belaban, Bukit Semujan Semangit Menyukung Melingkung, Embaloh Sibau watershed and Sungai Putri) were obtained from Bukit Baka Bukit Raya National Park, Betung Kerihun National Park, Danau Sentarum National Park, and West Kalimantan Natural Resources Conservation Agency, and land cover data were obtained from the Directorate General of Forestry and Environmental Planning of the Ministry of Environment and Forestry. The data obtained were analyzed using descriptive statistics, land cover analysis, and multiple linear regression analysis to test the relationship between orangutan population and eight variables, namely forest cover, shrubs (secondary regrowth), agriculture cover, open land, water body, road density, river density and settlement density. The results showed that orangutan population in the Bukit Semujan Semangit Menyukung Melingkung and Sungai Putri locations tended to increase. On the other hand, orangutan population in the Belaban and Embaloh Sibau watersheds tended to fluctuate. The land cover in the Belaban, Bukit Semujan Semangit Menyukung Melingkung and Sungai Putri tended to fluctuate, while that in Embaloh Sibau was steady. Bornean orangutan populations have a strong relationship with the extent of forest cover and shrubs. The findings of this study suggest that conserving the remaining forest and shrubs altogether with population monitoring, inventory of feed availability, and forest area patrol are imperative to protect and conserve orangutan population.